Two multinational, observational surveys investigating perceptions of beauty and attitudes and experiences relating to aesthetic medical procedures. (9th March 2020) - Redaelli, Alessio; Siddiqui Syed, Sana; Liu, Xierong; Poliziani, Michele; Erbil, Hakan; Prygova, Inna; Atamanov, Vasiliy
Abstract: Background: Data on opinions and experiences of aesthetic medical procedures outside the United States and Western Europe are scarce. Aims: This study aimed to survey users and non‐users of aesthetic procedures in countries where this information is less readily available, to understand attitudes and perceptions relating to beauty. Patients/Methods: Two independent internet‐based observational surveys were conducted. Survey 1: individuals from Colombia, Lebanon, Malaysia, Russia and Turkey who were 'users' or 'non‐users' of aesthetic medical procedures. Survey 2: individuals from Colombia, Russia, Thailand, Turkey and the United Arab Emirates who were 'users' of non‐surgical aesthetic treatments. Results: Surveys 1 and 2 were completed by 300 and 160 individuals, respectively, most of whom were female (94.0% and 99%). Overall, respondents rated the eyes and smile as the most pleasing male and female facial features. Most participants (mean 82.6%; range 75%‐100%) believed maintaining a healthy lifestyle was important for ageing gracefully, and over one‐third (36.0%; 28%‐47%) believed men age more gracefully than women. The emphasis respondents placed on the importance of physical attributes vs inner feelings, internal beauty and self‐confidence varied between countries. Users were often more positive about aesthetic medical procedure outcomes than non‐users. Adequate information, good physician communication (including managing treatment expectations), treatment recommendations based on patient need and good aftercare improved treatment satisfaction. Conclusions: The eyes and smile were key features of attractiveness, but maintaining a healthy lifestyle was consistently considered an important factor for ageing gracefully. Ensuring patients are well informed was a major determinant of treatment satisfaction.